Working with a secular age: interdisciplinary perspectives on Charles Taylor's master narrative - Zemmin, Florian; Jager, Colin; Vanheeswijck, Guido; Taylor, Charles (Religion and its others, 2016)
Charles Taylor’s monumental book A Secular Age has been extensively discussed, criticized, and worked on. This volume, by contrast, explores ways of working with Taylor’s book, especially its potentials and limits for individual research projects. Due to its wide reception, it has initiated a truly interdisciplinary object of study; with essays drawn from various research fields, this volume fosters substantial conversation across disciplines.
"This book grew out of a conference hosted by the Institute of Advanced Study in the Humanities and the Social Sciences (IASH) at the University of Bern from 5-8 March 2014 and entitled "Working with A Secular Age - Interdisciplinary Reflections on Charles Taylor's Conception of the Secular." (Preface)
Keywords: Konferenzschrift; Säkularisierung; Taylor, Charles / A secular age